2003
DOI: 10.1086/379235
|View full text |Cite
|
Sign up to set email alerts
|

Interferometer Observations of Subparsec-Scale Infrared Emission in the Nucleus of NGC 4151

Abstract: We report novel, high-angular resolution interferometric measurements that imply the near-infrared nuclear emission in NGC 4151 is unexpectedly compact. We have observed the nucleus of NGC 4151 at 2.2 µm using the two 10-meter Keck telescopes as an interferometer and find a marginally resolved source ≤ 0.1 pc in diameter. Our measurements rule out models in which a majority of the K band nuclear emission is produced on scales larger than this size. The interpretation of our measurement most consistent with oth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 30 publications
10
103
1
Order By: Relevance
“…2. Figure 3 shows the final calibrated visibilities for NGC 4151 as a function of the projected baseline length, enlarged in the left panel of the insets. We confirm the visibility level observed by Swain et al (2003). The covered range of projected baselines is very limited (note also that the shortest possible for NGC 4151 is ∼70 m due to the KI's delay line restriction).…”
Section: Observations and Data Reductionsupporting
confidence: 87%
See 1 more Smart Citation
“…2. Figure 3 shows the final calibrated visibilities for NGC 4151 as a function of the projected baseline length, enlarged in the left panel of the insets. We confirm the visibility level observed by Swain et al (2003). The covered range of projected baselines is very limited (note also that the shortest possible for NGC 4151 is ∼70 m due to the KI's delay line restriction).…”
Section: Observations and Data Reductionsupporting
confidence: 87%
“…While the brightest type 1 AGN NGC 4151 and type 2 AGN NGC 1068 have been observed by Swain et al (2003) and Wittkowski et al (2004), respectively, further exploration has been hampered mainly by technical difficulties. Here we report successful observations of four type 1 AGNs with the Keck interferometer (KI) in the near-IR (K-band 2.2 μm).…”
Section: Introductionmentioning
confidence: 99%
“…The Keck Interferometer observations of the Seyfert 1 nucleus of NGC 4151 (Swain et al 2003) showed that the majority of the central (∼3 pc) K-band light arises from very small scales of ≤0.1 pc, probably from the central accretion disk. Our K-band observations of the Seyfert 2 galaxy NGC 1068 show that only part of the central light arises from compact < ∼ 0.4 pc scales while another part arises from larger scales.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of optical/infrared interferometry to investigate AGN was recently discussed by Wittkowski et al (2003). Swain et al (2003) reported the first K-band interferometric observations of the Seyfert 1 galaxy NGC 4151 obtained with the 85 m baseline of the Keck Interferometer. Jaffe et al (2004) reported on the first mid-infrared interferometric observation of the dusty torus of NGC 1068 using VLTI/MIDI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the IR emission source in a small number of nearby type 1 and type 2 AGN have been resolved in the mid-IR with the interferometric instrument MIDI at the VLTI (Jaffe et al 2004;Tristram et al 2007;Beckert et al 2008;Raban et al 2009;Tristram et al 2009;Burtscher et al 2009) and in the near-IR with the Keck interferometer (Swain et al 2003;Kishimoto et al 2009a). While interferometry provides the most direct access to the torus structure and brightness distribution (Kishimoto et al 2009a), observations are limited to the brightest AGN that are in reach of current facilities.…”
Section: Introductionmentioning
confidence: 99%